2018
DOI: 10.1093/molbev/msy128
|View full text |Cite
|
Sign up to set email alerts
|

Recurrent Amplification of the Heterochromatin Protein 1 (HP1) Gene Family across Diptera

Abstract: The heterochromatic genome compartment mediates strictly conserved cellular processes such as chromosome segregation, telomere integrity, and genome stability. Paradoxically, heterochromatic DNA sequence is wildly unconserved. Recent reports that many hybrid incompatibility genes encode heterochromatin proteins, together with the observation that interspecies hybrids suffer aberrant heterochromatin-dependent processes, suggest that heterochromatic DNA packaging requires species-specific innovations. Testing th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
28
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 124 publications
2
28
0
Order By: Relevance
“…In Drosophila simulans, a young duplicate of heterochromatin protein 1 (HP1D) causes sex ratio meiotic drive (Montchamp-Moreau et al 2006;Helleu et al 2016), and HP1D (also known as rhino) is a key player in piRNA genome defense in D. melanogaster and presumably other species (Klattenhoff et al 2009). Furthermore, recurrent amplification of HP1 copies occurs in lineages where sex ratio drive is common (Helleu and Levine 2018). We identified multiple HP1 family members in the T. dalmanni genome, and one (the HP1E ortholog) was Xlinked, but it did not show signs of SR-associated divergence, differential expression or coverage.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Drosophila simulans, a young duplicate of heterochromatin protein 1 (HP1D) causes sex ratio meiotic drive (Montchamp-Moreau et al 2006;Helleu et al 2016), and HP1D (also known as rhino) is a key player in piRNA genome defense in D. melanogaster and presumably other species (Klattenhoff et al 2009). Furthermore, recurrent amplification of HP1 copies occurs in lineages where sex ratio drive is common (Helleu and Levine 2018). We identified multiple HP1 family members in the T. dalmanni genome, and one (the HP1E ortholog) was Xlinked, but it did not show signs of SR-associated divergence, differential expression or coverage.…”
Section: Discussionmentioning
confidence: 99%
“…In addition to the canonical piRNA genes, piwi, maelstrom, aubergine, and Argonaute3, we identified an additional 168 piRNArelated genes from three recent studies in D. melanogaster(Handler et al 2013;Palmer et al 2018;Ozata et al 2019) for further analysis. In addition, the Heterochromatin protein 1 family is expanding within diptera in association with meiotic drive(Helleu and Levine 2018) and is associated with de novo heterochromatic silencing near novel TE insertions(Lee and Karpen 2017). In Drosophila the HP1E family includes rhino (HP1E) which is a key piRNA gene in…”
mentioning
confidence: 99%
“…149 Similarly, disruption of the euchromatin mark H4K16ac-associated gene Sas2 or overexpression of the gene Sir3, which participates in the deacetylation in budding yeast, 150,151 leads to heterochromatin spreading. It has been demonstrated that the copy numbers and expression patterns of cHet-associated genes dramatically vary between species, 152,153 probably in response to the rapid evolution of repetitive DNA sequences (see below). This may result in the shift in boundaries between euchromatin and heterochromatin, reshaping the chromatin architecture of the entire genome.…”
Section: Evolution Of Heterochromatin and Its Associated Proteinsmentioning
confidence: 99%
“…157 The rapid evolution of heterochromatin must be contained to avoid impairing its important structural and regulatory functions. This is manifested as an "arms race" of sorts between heterochromatin and its regulatory proteins and RNAs, including those involved in heterochromatin packaging, 152,153 telomere protection, 158 and small RNA pathways. 159,160 These proteins either show an excess of amino acid change, that is, have the signature of positive selection, 161,162 or undergo rampant gene birth and death processes accompanied by newly evolved expression patterns that are usually restricted in the germline.…”
Section: Evolution Of Heterochromatin and Its Associated Proteinsmentioning
confidence: 99%
See 1 more Smart Citation